Synthesis and Structural Characterization of Y-doped Pyramidal ZnO Powders - İ.s. Yahıa; Süleyman Köytepe; Tankut Ates; Hanifi Kebiroglu; Havva Esma Okur; Niyazi Bulut; Omer Kaygili; Turgay Seçkin; Turan Ince; İsmail Ercan; Filiz Ercan (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2020)
The present study focuses on the structural changes in ZnO powder induced by doping of a rare earth metal of Y. For this aim, we synthesized four ZnO samples with different Y-content using the combustion reaction method. X-ray powder diffraction (XRPD) technique and scanning electron microscopy (SEM) results confirm that the as-investigated structural parameters and morphology of the ZnO structure were affected directly by the concentration of Y dopant. For each Y-doped sample, randomly-oriented pyramidal morphology and the formation of a minority phase of Y2O3 were observed. A gradual increase in both lattice parameters and unit cell volume was detected with increasing Y content. All samples were found to be thermally stable in the temperature interval of 25-950 °C.